Studies of the Effect of Heat Treatment on Stress-Produced Failure in Compressed Concrete - Hoła, J. (Engineering Transactions, 1992)
This paper points out that the fracture process of plain concrete subjected to lowpressure steam heat treatment is different from that of the normally cured concrete. This was established by tests carried out by the methods of acoustic emission and strain measurements. The tests revealed that heat-treated concrete displays a considerably lower fatigue strength and a slightly higher long-term strength. This fact should be taken into account both in planning the cycles of heat treatment of concrete or in designing the prefabricated concrete structures, the safety of which largely depends on fatigue strength.